2022
DOI: 10.3758/s13428-022-01920-6
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of a smartphone-based approach-avoidance task: Effects of retest period, stimulus type, and demographics

Abstract: The approach-avoidance task (AAT) is an implicit task that measures people’s behavioral tendencies to approach or avoid stimuli in the environment. In recent years, it has been used successfully to help explain a variety of health problems (e.g., addictions and phobias). Unfortunately, more recent AAT studies have failed to replicate earlier promising findings. One explanation for these replication failures could be that the AAT does not reliably measure approach-avoidance tendencies. Here, we first review exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 82 publications
2
10
2
Order By: Relevance
“… 26 Other studies using a mobile version of the AAT indicated that test-retest reliability across eight measurement occasions was low while split-half reliability was high, again indicating temporal fluctuations in approach biases. 27 This is in line with findings obtained from other indirect measures that showed modest stability over time. 28 Such within-subject fluctuations in biases are probably not only due to random variation, as approach-avoidance biases have been shown to decrease with after-meal-satiety in normal-weight individuals, and they have been shown to change based on individuals’ current affective states.…”
supporting
confidence: 89%
“… 26 Other studies using a mobile version of the AAT indicated that test-retest reliability across eight measurement occasions was low while split-half reliability was high, again indicating temporal fluctuations in approach biases. 27 This is in line with findings obtained from other indirect measures that showed modest stability over time. 28 Such within-subject fluctuations in biases are probably not only due to random variation, as approach-avoidance biases have been shown to decrease with after-meal-satiety in normal-weight individuals, and they have been shown to change based on individuals’ current affective states.…”
supporting
confidence: 89%
“…For RT-based food approach tendencies, internal consistencies (average Spearman-Brown corrected split-half reliabilities) were acceptable for basic research (r = .80) but higher than those generally reported in AAT-research (mean r = .52; Zech et al, 2022). We assessed test-retest reliability both based on the consistency of two single sessions (ICC_1;…”
Section: Reliabilitymentioning
confidence: 99%
“…Another indication of dynamic approach tendencies is that the AATs test-retest reliability is generally reported to be low, whereas its split-half reliability is generally reported to be high (Kahveci et. al., 2021;Machulska et al, 2022;Zech et al, 2022)-a pattern that indicates that a measure likely detects state changes (Hedge et al, 2018). If approach tendencies indeed fluctuate, overconsumption may be associated with a dysregulation of need-based fluctuations of approach tendencies, rather than chronically elevated approach tendencies.…”
Section: Dynamic Food Approach Tendenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevantfeature AAT, in contrast, directly manipulates the contingency between a task-relevant feature of the stimulus and the response, for example by measuring chocolate approachavoidance bias by requiring participants to approach chocolate stimuli during one block and to avoid it during another block. This task usually has a high reliability, from around .90 (Zech, Gable, van Dijk, & van Dillen, 2022), to around .70 (Hofmann, Friese, & Gschwendner, 2009;, up to .50 (Kahveci, Van Bockstaele, et al, 2020); however, the direct nature of its instructions make it easy for the participant to figure out what the task is about.…”
mentioning
confidence: 99%